Association between recanalization attempts and functional outcome after thrombectomy for large ischemic stroke - Winkelmeier, Laurens Paul; Faizy, Tobias D.; Broocks, Gabriel; Meyer, Lukas; Heitkamp, Christian; Brekenfeld, Caspar; Thaler, Christian; Steffen, Paul; Schell, Maximilian; Deb-Chatterji, Milani; Hanning, Uta; Kniep, Helge; et al. (Stroke, 2023)
BACKGROUND: - - Recently, 3 randomized controlled trials provided high-level evidence that patients with large ischemic stroke achieved better functional outcomes after endovascular therapy than with medical care alone. We aimed to investigate whether the clinical benefit of endovascular therapy is associated with the number of recanalization attempts in extensive baseline infarction. - - METHODS: - - This retrospective multicenter study enrolled patients from the German Stroke Registry who underwent endovascular therapy for anterior circulation large vessel occlusion between 2015 and 2021. Large ischemic stroke was defined as an Alberta Stroke Program Early Computed Tomography Score of 3 to 5. The study cohort was divided into patients with unsuccessful reperfusion (Thrombolysis in Cerebral Infarction score, 0-2a) and successful reperfusion (Thrombolysis in Cerebral Infarction score, 2b/3) at attempts 1, 2, 3, or ≥4. The primary outcome was favorable functional outcome defined as modified Rankin Scale score of 0 to 3 at 90 days. Safety outcomes were symptomatic intracranial hemorrhage after 24 hours and death within 90 days. Multivariable logistic regression was used to identify independent determinants of primary and secondary outcomes. - - RESULTS: - - A total of 348 patients met the inclusion criteria. Successful reperfusion was observed in 83.3% and favorable functional outcomes in 36.2%. Successful reperfusion at attempts 1 (adjusted odds ratio, 5.97 [95% CI, 1.71-24.43]; P=0.008) and 2 (adjusted odds ratio, 6.32 [95% CI, 1.73-26.92]; P=0.008) increased the odds of favorable functional outcome, whereas success at attempts 3 or ≥4 did not. Patients with >2 attempts showed higher rates of symptomatic intracranial hemorrhage (12.8% versus 6.5%; P=0.046). Successful reperfusion at any attempt lowered the odds of death compared with unsuccessful reperfusion. - - CONCLUSIONS: - - In patients with large vessel occlusion and Alberta Stroke Program Early Computed Tomography Score of 3 to 5, the clinical benefit of endovascular therapy was linked to the number of recanalization attempts required for successful reperfusion. Our findings encourage to perform at least 2 recanalization attempts to seek for successful reperfusion in large ischemic strokes, while >2 attempts should follow a careful risk-benefit assessment in these highly affected patients. - - REGISTRATION: - - URL: https://www.clinicaltrials.gov; Unique identifier: NCT03356392.